Level of winter protein supplementation for steer calves both wintered and summer grazed on bluestem pasture - Smith, E.F.; Koch, B.A.; Good, D.L.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
This is a progress report of the wintering phase of the third trial of this experiment. The results of the other two tests are reported in Circular 308 and elsewhere in this publication. The test is designed to study the level of protein supplementation most desirable for wintering steer calves to be sold off summer grass as stocker or feeder yearlings. Results of the experiment are measured by the combined winter and summer performance of the steers.
Keywords: Beef; Protein; Bluestem pasture; Performance